Exogenous protease supplementation to the diet enhances growth performance, improves nitrogen utilization, and reduces stress in finishing pigs. Issue 2 (6th May 2022) - Hoque, Md Raihanul; Song, Jun H.; Kim, In H.
Abstract: We have conducted this experiment to evaluate a new exogenous protease in finishing pigs' growth performance, nutrient digestibility, gas emission, blood profiles, and meat quality. A total of 200 pigs of 52.15 ± 2.31 kg average body weight (BW) were divided into four dietary treatments named as: CON, basal diet; TRT1, basal diet + 0.05% protease; TRT2, basal diet + 0.1% protease; TRT3, basal diet + 1.5% protease. Each treatment consisted of 10 pens, where five pigs were allotted to each pen according to their body weight and sex. The dietary treatments were allotted to the pens in a randomized block design. During this 10‐week‐long experiment, BW, average daily gain (ADG), average daily feed intake (ADFI), and gain to feed ratio (G:F) were calculated for Week 0–5, Week 6–10, and the overall period. During Week 6–10, ADG was higher in TRT2 and TRT3 than in the CON and TRT1 groups. At the same time, a linear increase was observed in ADG and G:F of the pigs. In addition, the final BW of pigs' was linearly increased by protease supplementation. On Week 10, there was a linear trend of increase ( p  = 0.0575) in crude protein digestibility and a trend of linear reduction ( p  = 0.0651) in NH3 gas emission. In blood profile, cortisol presented a linear decrease in both Week 5 ( p  = 0.251) and Week 10 ( p  = 0.0585). In addition, increasing doses of protease showed a trend of linear increase ( p  = 0.0592) in creatinine, whereas linear reduction was observed in the concentration of epinephrine ( p  = 0.0636) and norepinephrine ( p  = 0.0167) during Week 10. In conclusion, protease supplementation helped in improving daily gain in finishing pigs through protein digestibility with associated reduction of ammonia emission and blood stress hormones.